Protein and microbial determinations on worn contact lenses cleaned conventionally using the Lens2® automatic lens cleaner - Haliza Abdul Mutalib; Ahmad Rohi Ghazali; Noor Suhailah Ali (Penerbit UKM, 2008)
The accumulation of tear film proteins as well as microbes colonization onto worn contact lenses can be eliminated conventionally by mechanical rubbing during the cleaning process. Lens2® functions in rotation manner to loosen the deposits on the contact lens and has antimicrobial coating to keep lenses away from contamination. The objective of this study was to determine the efficiency of Lens2® to remove deposited protein and reduce microbial contamination compared to conventional method. Twenty-eight subjects each wore a pair of contact lens FDA Group 1 (Polymacon, SoftLens® 38, Bausch & Lomb) for one month and c l eaned them us ing mul t ipurpos e solut ion (COMPLETE ® MoisturePLUS TM , Advanced Medical Optics) separately using two different methods. The right lens was cleaned conventionally while the left lens were cleaned using the Lens2® The control group of thirteen subjects each . wore a pair of contact lens for the same period and cleaned both conventionally. These lenses and its cases were then analyzed for protein deposition using Bichinchoninic Acid Assay (BCA) Kit (Sigma, USA) in 96-well plate. Microbial contamination was determined by culturing the samples on nutrient agar for bacteria and fungi and non-nutrient agar for amoeba isolation. The mean of total protein on control lenses (17.014 ± 13.246 µg/mL) was not significantly different from those on the Lens2® (21.623 ± 19.127 µg/mL). There were also low growth numbers of amoeba in each group of samples. Interestingly, there were no growths of amoeba from all Lens2® samples collected. There was also low growth numbers of bacteria in each sample group whereby Lens2® had the lowest growth of bacteria. No growth of fungi was obtained from all samples. The automatic lens cleaner, Lens2® was found to be as efficient as the conventional cleaning method. However, the Lens2® has additional advantage Jurnal Sains Kesihatan Malaysia 6 (1) 2008: 11-2112 because of its antimicrobial material and need shorter time in the cleaning process as well as easy and effective.